A fully-coupled water-vapor flow and rock deformation/damage model for shale and coal: Its application for mine stability evaluation. (October 2021) - Liu, Ang; Liu, Shimin
Abstract: Roof instability is a pervasive hazard that may cause injuries and fatalities in underground coal mines. Variations in air humidity and the duration of roof exposure are known to significantly influence the stability of shale roof strata. Moisture-sensitive shales progressively deteriorate over time due to humidity-interaction and matrix swelling which can trigger skin failure and roof falls. Quantifying the evolution of dynamic mechanical and petrophysical properties of the shale roof requires a comprehensive understanding of the retention behavior of multiphase fluids in the shale and of the induced alterations associated with air-water-shale/coal interactions. This study presents a mechanism-based framework for modeling the integrative deformation and failure behaviors of the rock structure, shale roof and coal pillar—and integrates the coupled effects of water vapor flow, elastic deformation, and damage. A Time-Dependent Rock-Fluid-Geomechanics Model (TD-RFG Model) was developed to evaluate the time-dependent rock structure dynamics. The interactions across the elastic deformation field, the transient fluid transport field and the discontinuous damage field are analyzed and modeled using TD-RFG. The established TD-RFG platform provides a pathway for multi-field and time-dependent rock structure stability assessment. A case study of shaly roof stability in an Illinois Basin coal mine and an analysis of it are presented. In the analysis we investigate the time- and location-dependent propagation of rock fractures that create connected channels that allow for rapid water penetration. The analysis indicates that, because of damage-induced increases in permeabilities, moisture transport is facilitated and so seasonal relative humidity variations at the mine opening are quickly reflected at interior locations in the shale roof, coal pillars and ground floor. The results of the modeling can ultimately provide the approach and data for quantifying and evaluating the water retention behavior and suction potential in an unsaturated air-water-shale/coal system and define strategies for ground control.